Measurement of the field response of Musa genotypes to Radopholus similis and Helicotylenchus multicinctus and the implications for nematode resistance breeding - Hartman, J.B.; Vuylsteke, D.R.; Speijer, P.R.; Ssango, F.; Coyne, Danny L.; Waele, D. de (2010)
Crop growth and damage parameters (plant growth and yield, root damage and nematode population densities), believed to be associated with resistance of Musa genotypes to nematodes under field conditions, were evaluated in a field trial of 24 Musa genotypes inoculated at planting with a combination of Radopholus similis and Helicotylenchus multicinctus with the objective to identify parameters with strong association with nematode resistance and high heritability. Correlation and path analysis of the association between plant growth, yield, root damage and nematode population densities showed a strong negative association between percentage dead roots, percentage root necrosis, R. similis and H. multicinctus population densities and yield. The strongest negative association was observed between percentage dead roots and yield. Broad-sense genotype heritability estimates demonstrated that heritability estimates for percentage dead roots, number of large lesions and nematode population density were most affected by inoculation with nematodes. These results indicate therefore that effective selection for nematode resistance under field conditions could be obtained by using an index, that includes percentage dead roots, the number of large lesions, and nematode population density.